Osteosarcoma Cell-Derived Exosomal ELFN1-AS1 Mediates Macrophage M2 Polarization via Sponging miR-138-5p and miR-1291 to Promote the Tumorgenesis of Osteosarcoma - Wang, Bangmin; Wang, Xin; Li, Po; Niu, Xiaoying; Liang, Xiaoxiao; Liu, Guancong; Liu, Zhiyong; Ge, Hong (Frontiers in Oncology, 2022)
Background: Exosomes play an important role in cell-cell communication by transferring genetic materials such as long non-coding RNAs (lncRNAs) between cancer cells and tumor-associated macrophages (TAMs) in the tumor microenvironment (TME). Recent studies revealed that lncRNA ELFN1-AS1 could function as an oncogene in many human cancers. However, the role of extracellular lncRNA ELFN1-AS1 in cell-to-cell communication of osteosarcoma (OS) has not been fully investigated. Methods: Functional studies, including CCK-8, EdU staining and transwell assay were performed to investigate the role of ELFN1-AS1 in the progression of OS. 143B xenograft mouse model was established to assess the role of ELFN1-AS1 in vivo. In addition, transmission electron microscopy (TEM) and real-time quantitative PCR (RT-qPCR) assay were used to verify the existence of exosomal ELFN1-AS1. Results: The level of ELFN1-AS1 was markedly upregulated in patients with advanced OS and in OS cells. In addition, overexpression of ELFN1-AS1 significantly promoted the proliferation, migration and invasion of OS cells, while knockdown of ELFN1-AS1 exhibited the opposite effects. Meanwhile, ELFN1-AS1 could be transferred from OS cells to macrophages via exosomes. Exosomal ELFN1-AS1 from 143B cells was able to promote macrophage M2 polarization, and M2 macrophage in return facilitated OS progression. Mechanistically, overexpression of ELFN1-AS1 upregulated CREB1 level via sponging miR-138-5p and miR-1291 in macrophage. Conclusion: OS cell-derived exosomal ELFN1-AS1 was able to induce macrophage M2 polarization via sponging miR-138-5p and miR-1291, and M2 macrophage notably facilitated the progression of OS. These data suggested that ELFN1-AS1 might serve as a potential therapeutic target for osteosarcoma.